Illustrated catalogue of type specimens of Acridoidea and Pyrgomorphoidea (Insecta: Orthoptera) in the collection of Shaanxi Normal University - Yin, Xiongyan; Yang, Lu; Ji, Yonghao; Gan, Lijia; Li, Xiaoyu; Liu, Xuanzeng; Lin, Liliang; Huang, Yuan (Zootaxa, 2026)
Specimen collections serve as core archives for global biodiversity. Particularly during periods of massive species population decline, physical specimens remain irreplaceable for biodiversity research and conservation. In this era of rapid digital advancement, traditional value and digital potential of specimens resonate in synergy. Digitization further transforms them into resources accessible across time and space. Among these collection specimens, type specimens are of paramount importance, they not only serve as the basis for species naming (International Code of Zoological Nomenclature, ICZN), but also form as the core reference for morphological, biogeographical, and conservation biology research. Should their information be lost or the specimens themselves damaged, subsequent related studies would lose their verifiable foundation. Currently, despite the global surge in specimen digitization, most museums have yet to establish comprehensive digital management systems covering the entire workflow. Consequently, type specimen inventories remain essential foundational reference materials for taxonomists undertaking clade revision work. To address this, this paper compiles Orthoptera specimens in relatively good condition from the Zoological and Botanical Museum of Shaanxi Normal University (SNNU), providing detailed documentation of 140 specimens labeled as “types”. These specimens belong to Acridoidea and Pyrgomorphoidea, comprising 4 families, 14 subfamilies, and 69 genera. According to the International Code of Zoological Nomenclature (ICZN), the aforementioned 140 type specimens represent 140 valid species. This paper provides high–resolution illustrations and complete original literature for all taxonomic units, aiming to offer a systematic guide for taxonomic research on specimens of Acridoidea and Pyrgomorphoidea within the order Orthoptera.